2021
DOI: 10.5339/jemtac.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of telemedicine services for COVID-19 patients in “Al-Anbar” province west of Iraq

Abstract: Background: The rapid spread of COVID-19 disease in Iraq has been a daunting challenge. Given the overwhelmed Iraqi healthcare system, healthcare directors struggled to manage this unprecedented crisis. The role of telemedicine during the coronavirus pandemic has evolved to allow for social distancing while providing appropriate health care to the community at large. Telemedicine emerged as a reasonable solution to deliver appropriate care to COVID-19 and non-COVID-19 patients in the era of the COVID-19 pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Researchers in Anbar province found that patients with mild to moderate cases of covid-19 who utilized telemedicine health services had a lower risk of dying. (28). The mortality rate of patients treated outside the traditional healthcare system has been shown to be lower (29).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in Anbar province found that patients with mild to moderate cases of covid-19 who utilized telemedicine health services had a lower risk of dying. (28). The mortality rate of patients treated outside the traditional healthcare system has been shown to be lower (29).…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer indicates distal tissue necrosis to the affected artery, (8) while procalcitonin (PCT) indicates secondary bacterial infection (9) . Interleukin-6 6 (IL6) indicates hyperimmune reaction, a genet COVID-19 infection (10) .…”
Section: Introductionmentioning
confidence: 99%